Severe Gestational Low-Protein Intake Impacts Hippocampal Cellularity, Tau, and Amyloid-β Levels, and Memory Performance in Male Adult Offspring: An Alzheimer-Simile Disease Model? - Grigoletti-Lima, Gabriel Boer; Lopes, Marcelo Gustavo; Franco, Ana Tereza Barufi; Damico, Aparecida Marcela; Boer, Patrìcia Aline; Rocha Gontijo, José Antonio (JAD reports, 2022)
Background: Maternal undernutrition has been associated with psychiatric and neurological disorders characterized by learning and memory impairment. Objective: Considering the lack of evidence, we aimed to analyze the effects of gestational protein restriction on learning and memory function associated with hippocampal cell numbers and neurodegenerative protein content later in life. Methods: Experiments were conducted in gestational low- (LP, 6% casein) or regular-protein (NP, 17% casein) diet intake offspring. Behavioral tests, isolated hippocampal isotropic fractionator cell studies, immunoblotting, and survival lifetime were observed. Results: The birthweight of LP males is significantly reduced relative to NP male progeny, and hippocampal mass increased in 88-week-old LP compared to age-matched NP offspring. The results showed an increased proximity measure in 87-week-old LP compared to NP offspring. Also, LP rats exhibited anxiety-like behaviors compared to NP rats at 48 and 86-wk of life. The estimated neuron number was unaltered in LP rats; however, non-neuron cell numbers increased compared to NP progeny. Here, we showed unprecedented hippocampal deposition of brain-derived neurotrophic factor, amyloid-β peptide (Aβ), and tau protein in 88-week-old LP relative to age-matched NP offspring. Conclusion: To date, no predicted studies showed changes in hippocampal morphological structure in maternal protein-restricted elderly offspring. The current data suggest that gestational protein restriction may accelerate hippocampal function loss, impacting learning/memory performance, and supposedly developing diseases similar to Alzheimer’s disease (AD) in elderly offspring. Thus, we propose that maternal protein restriction could be an elegant and novel method for constructing an AD-like model in adult male offspring.